Barriers to medication adherence by caregivers of children with leukemia: an observational study - Fernanda Alves França; Ana Catarina Fernandes Figueredo; Luiza Tessmann; Valdenize Tiziani; José Carlos Martins Córdoba; Isis Magalhães; Noêmia Urruth Leão Tavares; Patrícia Medeiros-Souza (Sociedade de Pediatria de São Paulo, 2023)
ABSTRACT Objective: To identify barriers to adherence to home oral maintenance chemotherapy in children with leukemia treated at a specialized cancer center. Methods: We used the Brief Medication Questionnaire (BMQ) as a tool for screening barriers to adherence. The level of adherence was calculated considering at least one positive response in each BMQ domain, defined as Regimen Screen, Belief Screen, and Recall Screen. A positive screening for belief barriers (PSB) indicates that the caregiver reports not understanding the medication's mechanism of action and adverse effects. Results: Three important barriers to adherence were identified: beliefs, number of children of the caregiver, and age of the caregiver. The primary caregivers included 32 mothers (80%), four fathers (10%), three grandmothers (7.5%), and one unrelated caregiver (2.5 %). Most caregivers with a PSB were mothers. A PSB indicates that the caregiver reports not understanding the medication's mechanism of action and adverse effects. Caregivers with two or more children (median, three) had more barriers to adherence. Caregivers with potential non-adherence tended to be older than those with potential adherence, although without statistical significance (p=0.079, Mann-Whitney U test). Conclusions: The main barriers to adherence to home oral maintenance chemotherapy in children with leukemia identified through interviews with their caregivers, most often mothers, were lack of understanding of the treatment regimen, a greater number of children, and older age.